2016
DOI: 10.19104/jepm.2016.114
|View full text |Cite
|
Sign up to set email alerts
|

Death from Cardiovascular Diseases and Air Pollution in Shiraz, Iran (March 2006-March 2012)

Abstract: Background: There is evidence that shows exposure to air pollution

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 36 publications
1
15
1
Order By: Relevance
“…In this study, there was a positive and strong significant re lationship between NO 2 and cardiovascular deaths in the case of under 18-year-olds after 11-day lags. In this regard, in Dadbakhsh et al's study, in Shiraz, Iran, the results showed that NO and NO X had a direct and significant rela tion with total cardiovascular deaths, and female deaths in the same month and total cardiovascular deaths that hap pened one month later [2]. In the study from China, nitro gen dioxide was also associated with an increase in isch emic heart disease death [41].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In this study, there was a positive and strong significant re lationship between NO 2 and cardiovascular deaths in the case of under 18-year-olds after 11-day lags. In this regard, in Dadbakhsh et al's study, in Shiraz, Iran, the results showed that NO and NO X had a direct and significant rela tion with total cardiovascular deaths, and female deaths in the same month and total cardiovascular deaths that hap pened one month later [2]. In the study from China, nitro gen dioxide was also associated with an increase in isch emic heart disease death [41].…”
Section: Discussionmentioning
confidence: 92%
“…Nowadays, various natural and ar tificial sources have caused changes in the physical and chemical properties of ambient air and have caused "air pollution" [1,2]. Air pollutants have a wide range of im pacts on human health and are considered to be one of the major environmental health issues in megaindustrial world cities [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies about the effects of air pollutants indicate that air pollution has also caused deaths and hospital admissions due to heart disease and road accidents in Iran [ 31 – 36 ]. This evidence further shows the importance of controlling air pollution in this country.…”
Section: Discussionmentioning
confidence: 99%